A Plant-Based Dietary Intervention Improves Beta-Cell Function and Insulin Resistance in Overweight Adults: A 16-Week Randomized Clinical Trial - Kahleova, Hana; Tura, Andrea; Hill, Martin; Holubkov, Richard; Barnard, Neal D (Nutrients, 2018)
The aim of this study was to test the effect of a plant-based dietary intervention on beta-cell function in overweight adults with no history of diabetes. Participants (n = 75) were randomized to follow a low-fat plant-based diet (n = 38) or to make no diet changes (n = 37) for 16 weeks. At baseline and 16 weeks, beta-cell function was quantified with a mathematical model. Using a standard meal test, insulin secretory rate was calculated by C-peptide deconvolution. The Homeostasis Model Assessment (HOMA-IR) index was used to assess insulin resistance while fasting. A marked increase in meal-stimulated insulin secretion was observed in the intervention group compared with controls (interaction between group and time, Gxt, p < 0.001). HOMA-IR index fell significantly (p < 0.001) in the intervention group (treatment effect -1.0 (95% CI, -1.2 to -0.8); Gxt, p = 0.004). Changes in HOMA-IR correlated positively with changes in body mass index (BMI) and visceral fat volume (r = 0.34; p = 0.009 and r = 0.42; p = 0.001, respectively). The latter remained significant after adjustment for changes in BMI (r = 0.41; p = 0.002). Changes in glucose-induced insulin secretion correlated negatively with BMI changes (r = -0.25; p = 0.04), but not with changes in visceral fat. Beta-cell function and insulin sensitivity were significantly improved through a low-fat plant-based diet in overweight adults.
Keywords: senioři; index tělesné hmotnosti; beta-buňky; Absorptiometry, Photon; Diet, Vegan; Weight Loss; beta-cell function; Obesity; adipozita; nitrobřišní tuk; sekrece inzulinu; inzulin; Middle Aged; mužské pohlaví; Insulin; energetický příjem; Energy Intake; Insulin Secretion; diet; District of Columbia; Adult; Overweight; Diet, Fat-Restricted; vegan; redukční dieta; Body Mass Index; Adiposity; dieta veganská; ženské pohlaví; Humans; Intra-Abdominal Fat; hmotnostní úbytek; nutrition; dieta s omezením tuků; Insulin-Secreting Cells; lidé středního věku; postprandiální období; Postprandial Period; absorpční fotometrie; obezita; nadváha; dospělí; inzulinová rezistence; Female; Aged; Insulin Resistance; diabetes; Diet, Reducing; lidé; Male